Strategi Pemulihan dan Penguatan Bahasa Ibu: Studi Kasus pada Perubahan Penggunaan Bahasa Bali di Masyarakat Bali - Widiantana, I Kadek (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2024)
Balinese, as the mother tongue of the Balinese people, faces challenges in its survival. Although the number of Balinese speakers is still relatively large, there is an alarming shift among the younger generation in the use of this language. This phenomenon creates the need for more serious efforts to strengthen the position of the Balinese language, especially in the family environment and early education. The method used in this research is a qualitative descriptive approach, with data collection carried out through a literature review. Analysis shows that Balinese is included in the category of endangered languages according to language typology by Michel Krauss. The use of Balinese as the language of instruction in initial education at school level is also an important focus. However, national policies and globalization pressures often lead to a decline in the use of regional languages in schools. The importance of using the mother tongue in education, especially at the initial level, has been supported by international organizations such as UNESCO. Efforts to strengthen the Balinese language can be carried out through several strategies, including strengthening the use of the Balinese language in the family environment, using Balinese as the language of instruction in schools at the educational level beginning, holding family-level Balinese language competitions, and reviving the "Dina Mabasa Bali" program as part of a policy that strengthens the habit of using the Balinese language. Through these steps, it is hoped that the existence of the Balinese language as the mother tongue of the Balinese people can be maintained and strengthened.